Susy breaking soft terms in the supersymmetric Pati-Salam landscape from intersecting D6-branes - Mudassar Sabir; Adeel Mansha; Tianjun Li; Zhi-Wei Wang (Journal of High Energy Physics)
Abstract We investigate the supersymmetry breaking soft terms for all the viable models in the complete landscape of three-family supersymmetric Pati-Salam models arising from intersecting D6-branes on a 𝕋6 /(ℤ2 × ℤ2) orientifold in type IIA string theory. The calculations are performed in the general scenario of u-moduli dominance with the s-moduli turned on, where the soft terms remain independent of the Yukawa couplings and the Wilson lines. The results for the trilinear coupling, gaugino-masses, squared-mass parameters of squarks, sleptons and Higgs depend on the brane wrapping numbers and the susy breaking parameters. We find that unlike the Yukawa couplings which remain unchanged for the models dual under the exchange of two SU(2) sectors, the corresponding soft term parameters only match for the trilinear coupling and the mass of the gluino. This can be explained by the internal geometry where the Yukawa interactions depend only on the triangular areas of the worldsheet instantons while the soft terms have an additional dependence on the orientation-angles of D6-branes in the three two-tori. In the special limit of parameter space we find universal masses for the Higgs and the gauginos.